Acculturation and Plasma Fatty Acid Concentrations in Hispanic and Chinese-American Adults: The Multi-Ethnic Study of Atherosclerosis. - Cassandra S Diep; Rozenn N Lemaitre; Tzu-An Chen; Tom Baranowski; Pamela L Lutsey; Ani W Manichaikul; Stephen S Rich; David E St-Jules; Brian T Steffen; Michael Y Tsai; David S Siscovick; Alexis C Frazier-Wood (PLoS ONE)
Background Acculturation to the U.S. is associated with increased risk of cardiovascular disease, but the etiologic pathways are not fully understood. Plasma fatty acid levels exhibit ethnic differences and are emerging as biomarkers and predictors of cardiovascular disease risk. Thus, plasma fatty acids may represent one pathway underlying the association between acculturation and cardiovascular disease. We investigated the cross-sectional relationship between acculturation and plasma phospholipid fatty acids in a diverse sample of Hispanic- and Chinese-American adults. Methods and findings Participants included 377 Mexican, 320 non-Mexican Hispanic, and 712 Chinese adults from the Multi-Ethnic Study of Atherosclerosis, who had full plasma phospholipid assays and acculturation information. Acculturation was determined from three proxy measures: nativity, language spoken at home, and years in the U.S., with possible scores ranging from 0 (least acculturated) to 5 (most acculturated) points. α-Linolenic acid, linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and arachidonic acid were measured in fasting plasma. Linear regression models were conducted in race/ethnicity-stratified analyses, with acculturation as the predictor and plasma phospholipid fatty acids as the outcome variables. We ran secondary analyses to examine associations between acculturation and dietary fatty acids for comparison. Covariates included age, gender, education, and income. Contrary to our hypothesis, no statistically significant associations were detected between acculturation and plasma phospholipid fatty acids for Chinese, non-Mexican Hispanic, or Mexican participants. However, acculturation was related to dietary total n-6 fatty acids and dietary n-3/n-6 ratios in expected directions for Mexican, non-Mexican Hispanic, and combined Hispanic participants. In Chinese individuals, acculturation was unexpectedly associated with lower arachidonic acid intake. Conclusion Absence of associations between acculturation and plasma phospholipid fatty acids suggests that changes in the plasma phospholipid fatty acids studied do not account for the observed associations of acculturation to the U.S. and cardiovascular disease risk. Similar findings were observed for eicosapentaenoic acid and docosahexaenoic acid, when using dietary intake. However, the observed associations between dietary n-6 fatty acids and acculturation in Hispanic individuals suggest that dietary intake may be more informative than phospholipids when investigating acculturation effects. In Chinese individuals, acculturation may have a possible protective effect through decreased arachidonic acid intake. Further research on dietary fatty acids and other cardiovascular disease biomarkers is needed to identify possible etiologic mechanisms between acculturation and cardiovascular disease.